Intracavitary ultrasound (ICARUS): a neuroendoscopic adaptation of intravascular ultrasound for intracerebral hemorrhage evacuation. (21st March 2018) - Chartrain, Alexander G; Hom, Danny; Bederson, Joshua B; Mocco, J; Kellner, Christopher Paul
Abstract : Neurosurgeons performing intracerebral hemorrhage evacuation procedures have limited options for monitoring hematoma evacuation and assessing residual hematoma burden intraoperatively. Here, we report the successful neuroendoscopic adaptation of intravascular ultrasound, referred to here as intracavitary ultrasound (ICARUS), in two patients. Pre-evacuation ICARUS demonstrated dense hematomas in both patients. Post-evacuation ICARUS in patient 1 demonstrated significant reduction in clot burden and two focal hyperechoic regions consistent with pockets of hematoma not previously seen with the endoscope or burr hole ultrasound. These areas were directly targeted and resected with the endoscope and suction device. Post-evacuation ICARUS in patient 2 showed significant reduction of hematoma volume without indication of residual blood. ICARUS findings were confirmed on intraoperative DynaCT and postoperative CT 24 hours later. ICARUS is feasibly performed in a hematoma cavity both before and after hematoma aspiration. ICARUS may provide additional information to the operating surgeon and assist in maximizing hematoma removal.